2010
DOI: 10.1101/sqb.2010.75.011
|View full text |Cite
|
Sign up to set email alerts
|

Space and Time in the Nucleus: Developmental Control of Replication Timing and Chromosome Architecture

Abstract: All eukaryotic cells replicate segments of their genomes in a defined temporal sequence. In multicellular organisms, at least half of the genome is subject to changes in this temporal sequence during development. We now know that this temporal sequence and its developmentally regulated changes are conserved across distantly related species, suggesting that it either represents or reflects something biologically important. However, both the mechanism and the significance of this program remain unknown. We recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
77
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 58 publications
1
77
0
Order By: Relevance
“…The timing of DNA replication is a fundamental aspect of genome metabolism that correlates with, and has been proposed to regulate, chromatin structure, gene expression, DNA repair, and cellular differentiation (Goren and Cedar 2003;Gilbert et al 2010). Replication timing is determined by the timing of replication origin firing (Rhind and Gilbert 2013).…”
mentioning
confidence: 99%
“…The timing of DNA replication is a fundamental aspect of genome metabolism that correlates with, and has been proposed to regulate, chromatin structure, gene expression, DNA repair, and cellular differentiation (Goren and Cedar 2003;Gilbert et al 2010). Replication timing is determined by the timing of replication origin firing (Rhind and Gilbert 2013).…”
mentioning
confidence: 99%
“…A second possible source of heterogeneity arises from the presence of multiple cell types in the root meristem region, as individual cell types might have different timing programs. Between any two cell types of human or mouse differentiated embryonic stem cells, up to 20% of the genome changes replication time (Hiratani et al, 2008;Gilbert et al, 2010;Hansen et al, 2010;Ryba et al, 2010). It has also been reported that 12% of the genome of human primary erythroblasts exhibits allele-specific differences in replication time, highlighting a third potential source of timing heterogeneity.…”
Section: Temporal Order Of Dna Replicationmentioning
confidence: 99%
“…This prolongation of S phase is the result of a shift from a mode where all regions of the DNA are replicated nearly simultaneously (Blumenthal et al 1974) to a mode where the replication of repetitive satellite sequences is delayed until later in S phase . Shifts in replication timing occur in many metazoans as cells become more specified, including Drosophila, Xenopus (Walter and Newport 1997), and mammals (Gilbert et al 2010). In the new mode of replication, the bulk of the DNA replicates in the first 15 min of S phase, but satellite sequences exhibit an ordered sequence of replication that occurs later, from 5 to 50 min in S phase .…”
mentioning
confidence: 99%